PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING BERBASIS PENILAIAN PORTOFOLIO TERHADAP KOMPETENSI PENGETAHUAN IPA - Dw Ayu Prami Handayani Dewi (Universitas Pendidikan Ganesha, 2018)
This research has an aim to determine the impact of CTL approach based on the portfolio assessment on science knowledge competence of grade V students Gugus I Gusti Ngurah Rai Denpasar Selatan of the academic year 2017/2018. This type of research is an experiment using Non-equivalent control group design research plan. The population of this research is all grade V students Gugus I Gusti Ngurah Rai with the total number of 263 students. The determination of the sample in this research is using random sampling technique with random class. The sample of the research is the student of grade Vc SDN 4 Sanur with the total amount 35 students as an experiment group and the grade V student SDN 8 Sanur with the total of 41 students as a control group. The competence data of science knowledge competence was collected by instruments in the form of multiple choice objective tests with 32 test items that has been validated. The data obtained were analyzed using statistic-descriptive method and statistic-inferential method, afterwards hypothesis test using (t) test. The result of the analysis data obtained thitung = 5,955 meanwhile, at the level of significance 5% and dk = 74 obtained score ttabel = 2,000 therefore, thitung = 5,955 > ttabel = 2,000. The average of science knowledge competence of an experiment group student = 78,00 > = 67,28 control group. Therefore, It can be concluded that the CTL approach based on the portfolio assessment has an effect on the science knowledge competence of the students of grade V Gugus I Gusti Ngurah Rai Denpasar Selatan Academic Year 2017/2018. Keywords : CTL, portfolio assessment, science knowledge competence.